Reference Values for Pulse Wave Doppler and Tissue Doppler Imaging in Pediatric Echocardiography. (February 2015) - Dallaire, Frederic; Slorach, Cameron; Hui, Wei; Sarkola, Taisto; Friedberg, Mark K.; Bradley, Timothy J.; Jaeggi, Edgar; Dragulescu, Andreea; Har, Ronnie L.H.; Cherney, David Z.I.; Mertens, Luc
<x xml:space="preserve">Abstract</x> Background— In pediatric echocardiography, pulse wave Doppler, and tissue Doppler imaging velocities are widely used to assess cardiac function. Current reference values and Z scores, allowing adjustment for growth are limited by inconsistent methodologies and small sample size. Using a standardized approach for parametric modeling and Z score quality assessment, we propose new pediatric reference values and Z score equations for most left ventricular pulse wave Doppler and tissue Doppler imaging measurements. Methods and Results— Two hundred thirty-three healthy pediatric subjects 1 to 18 years of age were prospectively recruited. Thirteen pulse wave Doppler and 14 tissue Doppler imaging measurements were recorded. Normalization for growth was done via a complete and standardized approach for parametric nonlinear regression modeling. Several analyses were performed to ensure adequate Z score distribution and to detect potential residual associations with growth or residual heteroscedasticity. Most measurements adopted a nonlinear relationship with growth and displayed significant heteroscedasticity. Compared with age, height, and weight, normalization for body surface area was most efficient in removing the effect of growth. Generally, polynomial and allometric models yielded adequate goodness-of-fit. Residual values for several measurements had significant departure from the normal distribution, which could be corrected using logarithmic or reciprocal transformation. Overall, weighted parametric nonlinear models allowed us to compute Z score equations with adequate normal distribution and without residual association with growth. Conclusions— We present Z scores for normalized pulse wave Doppler and tissue Doppler imaging in pediatric echocardiography. Further studies are needed to define the threshold beyond which health becomes a disease by integrating other important factors such as ventricular morphology, loading conditions, and heart rate.